Access (the modern paradox): a student clinic law hub re-scripting the border between institutional infrastructure and the public realm, in Braamfontein, Johannesburg - Norwood-Young, James (My University, 2016)
Abstract: Access (the modern paradox): Borders, much like Architecture, can be described in one of two ways. The one is the simple way, and the other a more complex – but unsettling – way that is open to contradiction. On the surface, a border is a threshold or boundary that constrains the separation of two or more entities. Yet, the more complex understanding is harder to define and because of that it requires limitations, or a different point of view to be able to comprehend. In the case of defining architecture, it can be seen that Architecture is: the art and science of building. Although, this isn’t actually the case, if it was the case practicing Architecture and designing buildings would be easy. There is a complex, more pluralistic way of interrogating Borders and Architecture. Put simply, borders define themselves in the eye of their user. This means that a border to a sociologist, or anthropologist, will be read in a completely different way to an engineer, or will be read differently by a geographer to an immigrant. It becomes obvious that there can never be a complete, all encompassing understanding of what a border is, or can be. A border will always be limited in one way or another, and will always be contested once it has been mapped on to paper. Could there possibly be a way to subvert, dilute or transgress a border or the notion of a border though architecture? Is there an architectural intervention, either physical or metaphysical, that could take on the role of the subversive, dilutor or transgressor? Can a border become actionable and create a place of ACCESS?
Keywords: City planning--South Africa--Johannesburg; Public space--South Africa--Johannesburg